PENGEMBANGAN MODUL PEMBELAJARAN FISIKA BERBASIS CONTEXTUAL TEACHING AND LEARNING (CTL) PADA POKOK BAHASAN RANGKAIAN ARUS SEARAH DI SMA - Yuliske Yuliske; Singgih Bektiarso; Sudarti Sudarti (FKIP Universitas Jember, 2019)
Abstract The objectives of this study are: 1) developing contextual teaching and learning (CTL) based physics modules on the subject of direct current series in high school, 2) testing the validation of contextual teaching and learning (CTL) based physics modules on the subject of direct current series in high school , 3) testing the effectiveness of contextual teaching and learning (CTL) based physics modules on the subject of a series of direct current in high school. This study uses research and development procedures according to Nieven (2006) which includes 3 stages, namely: (1) Preliminary research (2) Prototype stage, and (3) Assessment Phase. The instruments used in this study were validation sheets and formative tests in the form of description of pre-test and post-test questions. Based on the results of the validation analysis, the validity category is very valid with a reliability coefficient of 93.06%. The results of the field test analysis obtained an average N-Gain score of 0.71 so that the module was declared effective for use in learning direct current circuit material for class XII Science. Keywords : Contextual teaching and learning , Validation, Effectiveness.